Sources and strategies of legal research - Osborne, Caroline L. (Durham, North Carolina : Carolina Academic Press, LLC, 2023)
"Sources and Strategies of Legal Research, intended for use in first-year legal writing and research courses, offers a new approach to the course subject matter based on the concept that legal analysis is essential to legal research. This concise book is unique in two ways: it places legal analysis as the focal point of legal research; and it departs from the typical source-specific or bibliographical approach, instead taking a process-oriented approach, focusing on search strategies for efficiently and effectively finding information"--
Authority and the court system -- Legal analysis and legal research -- Research planning - creating a research strategy and documenting your research -- Legal citation -- The judicial opinion -- Statutes and constitutions -- Rules and regulations -- The legal encyclopedia -- Restatements of law -- The legal periodical -- American law reports -- Treatise -- The legal dictionary, publications for law students and finding aids -- The citator -- Find by citation and find by cross-reference -- The index and table of contents -- Researching using the popular names table -- Researching with citators -- Topic and key number/ researching with digests -- Terms and connector searching -- Summary of search strategies -- Compiling the legislative history.
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Includes bibliographical references and index.
Keywords: Legal research -- United States